A Stable Lithium–Oxygen Battery Electrolyte Based on Fully Methylated Cyclic Ether. (25th January 2019) - Huang, Zhimei; Zeng, Haipeng; Xie, Meilan; Lin, Xing; Huang, Zhaoming; Shen, Yue; Huang, Yunhui
Abstract: Ether‐based electrolytes are commonly used in Li–O2 batteries (LOBs) because of their relatively high stability. But they are still prone to be attacked by superoxides or singlet oxygen via hydrogen abstract reactions, which leads to performance decaying during long‐term operation. Herein we propose a methylated cyclic ether, 2, 2, 4, 4, 5, 5‐hexamethyl‐1, 3‐dioxolane (HMD), as a stable electrolyte solvent for LOBs. Such a compound does not contain any hydrogen atoms on the alpha‐carbon of the ether, and thus avoids hydrogen abstraction reactions. As the result, this solvent exhibits excellent stability with the presence of superoxide or singlet oxygen. In addition the CO2 evolution during charge process is prohibited. The LOB with HMD‐based electrolyte was able to run up to 157 cycles, 4 times more than with 1, 3‐dioxolane (DOL) or 1, 2‐dimethoxyethane (DME) based electrolytes. Abstract : Aggressiven Spezies keine Chance : Ein vollständig methyliertes 4, 4, 5, 5‐Hexamethyl‐1, 3‐dioxolan wurde als Elektrolytlösungsmittel für Li‐O2 ‐Batterien entwickelt. Der cyclische Ether ist hoch stabil in der Gegenwart von Superoxid oder Singulett‐Sauerstoff, weil alle aktiven α‐H‐Atome durch Methylgruppen ersetzt sind. Die Zyklenstabilität ist 4‐mal größer als mit konventionellen Etherelektrolyten.